Innovative Approaches In Tni's Territorial Development To Utilize The Demographic Dividend For The Realization Of Indonesia's Golden 2045 Vision - Dudih Ernawan; Pujo Widodo; I Gede Sumertha K.Y; Arifuddin Uksan (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
This research examines innovations in territorial development by the Indonesian National Armed Forces (TNI) in response to the demographic bonus with the goal of achieving the Indonesia Emas 2045 (Golden Indonesia 2045) vision. The study explores the phenomena and approaches used in leveraging demographic potential as a means to achieve long-term national development objectives. The research findings provide insights into the challenges and opportunities faced by the TNI in implementing territorial innovations and the implications of these efforts for realizing the Indonesia Emas 2045 vision. TNI's territorial development must adopt a comprehensive and forward-looking approach. It plays a pivotal role in preparing the younger generation to contribute to the realization of the Indonesia Emas 2045 vision. Through innovative methods, empowerment, and education that emphasize positive values, the younger generation can become agents of change who are competitive, ethically grounded, and dedicated to advancing Indonesia as a developed nation and playing a significant role on the global stage.